Systems Biology: To Meet Challenges for Biology in the Twenty-first Century - Pandurangan, Sundaramurthy; Gakkhar, Sunita (Research in Biotechnology, 2010)
Genomics, structural biology, and bioinformatics deal with identification, cataloguing and characterization of the components that make up a cell. The focus on individual genes and proteins, which has proven so powerful for the molecular genetics in the past century, is in itself inadequate to describe the dynamic processes involving interactions among tens, hundreds and even thousands of components. Cell function, including growth, differentiation, division, and apoptosis, are temporal processes and we will only be able toÃ‚Â understand them if we treat them as dynamic systems. There is a general agreement that systems approach is necessary to understand the causal and functional relationships that generate the dynamics of biological networks and pathways.